Potention of Giving Earth-Worm Food Lumbricus rubellus Toward Colour Alteration To The Guppy Poecilia reticulata - Zohra Hasyim; Ambeng Ambeng; Irma Andriani; Andi Rismayani Saputri (Universitas Hasanuddin, 2018)
The research entitled “Potention of Giving Earth-Worm Food Lumbricus rubellus Toward Colour Alteration to The Guppy Fish Poecilia reticulata” was aimed to find the influence of earth-worm Lumbricus rubellus extra increment toward colour alteration to the guppy fish Poecilia reticulata. The research was conducted for a month using three kind treatments of food, those were W0 (food composed of fish meal without earth-worm, Lumbricus rubellus), W1 (composed of fish meal with earth-worm Lumbricus rubellus), and W2 (composed of earth-worm Lumbricus rubellus without fish meal). The available aquariums were 3 units with sized 12cm x 20cm x 20 cm. The cultivated test fish (± 3 cm) were acclimated for 2 days. Three test fish placed into three experiment aquarium each. Formulation of food intake was 3% based on the weight of the fish and was given 2 times a day. The parameter of water quality measured in this research were temperature, pH, and dissolved oxygen (DO). Data analysis using henry and grime formula (1993). The result of the research showed that there was an increasing of caratenoid in guppy fish Poecilia reticulata for each treatment of W0, W1 and W2 treatments. The high carotenoid increasing occured in W2.